Evaluation of real-time polymerase chain reaction for detection of the 16s ribosomal RNA gene of mycobacterium tuberculosis and the diagnosis of cervical tuberculous lymphadenitis in a country with a high tuberculosis incidence - Patcharasarn Linasmita (2018)
Background.Tuberculous lymphadenitis (TBL) is the most common form of extrapulmonary tuberculosis. Currently, the standard diagnostic test for TBL is culture, which takes more than several weeks to yield results. We studied a real-time polymerase chain reaction (PCR) for rapid detection of Mycobacterium tuberculosis in cervical lymph node specimens obtained from patients in a country where the tuberculosis incidence is high.Methods.Patients with cervical lymphadenopathy were prospectively enrolled between April 2009 and March 2010. Clinical specimens obtained through fine-needle aspiration (FNA) and excisional biopsy were tested for M. tuberculosis by the COBAS TaqMan MTB Test, a real-time PCR assay for detecting the 16S ribosomal RNA gene of M. tuberculosis. Mycobacterial culture and histopathological findings from tissue biopsy specimens were used as a reference standard for sensitivity and specificity calculations.Results.Of 73 patients, 41 received a diagnosis of TBL. For biopsy specimens, the sensitivity of real-time PCR was 63.4, and the specificity was 96.9. For FNA specimens, the sensitivity was 17.1, and the specificity was 100. The sensitivity of real-time PCR of biopsy specimens was comparable to that of tissue culture but significant lower than that of histopathological examination (P < . 01).Conclusions.Real-time PCR did not increase the yield for rapid diagnosis of TBL. © 2012 The Author.